Acidentes por lepidópteros (larvas e adultos de mariposas): estudo dos aspectos epidemiológicos, clínicos e terapêuticos - Cardoso, Alberto Eduardo Cox; Haddad Júnior, Vidal [UNESP] (Sociedade Brasileira de Dermatologia, 2005)
Os autores apresentam e discutem aspectos dos acidentes causados por larvas de lepidópteros (mariposas), enfatizando as manifestações dermatológicas e a dor intensa que caracterizam estes agravos. Além disso, são apresentadas larvas de mariposas que causam manifestações extracutâneas, tais como severos distúrbios de coagulação e artropatias anquilosantes, e ainda dermatites provocadas por insetos adultos. Os principais grupos de lepidópteros causadores de acidentes em humanos são demonstrados, e as medidas terapêuticas atualizadas são discutidas. O lepidopterismo e o erucismo são acidentes comuns, e é importante que o dermatologista saiba reconhecer e tratar esse tipo de envenenamento.

The authors present and discuss some aspects of injuries caused by larvae of Lepidoptera (moths), emphasizing the skin manifestations and intense pain that characterize these conditions. Moreover, they present moth larvae that cause extracutaneous manifestations, such as severe coagulation disorders and ankylosing arthropathies, and dermatitis related to adult insects. The main groups of Lepidoptera that cause injuries in humans are presented as well as current therapeutic alternatives. Lepidopterism and erucism are common accidents and it is important that dermatologists be aware and able to recognize and treat this kind of poisoning.
Accidents caused by lepidopterans (moth larvae and adult): study on the epidemiological, clinical and therapeutic aspects
Keywords: Animais venenosos; Envenenamento; Lepidópteros; Mariposa; Mordeduras e picadas de insetos; Venomous animals; Envenomation; Lepidoptera; Moths; Insect bites and stings